2019
DOI: 10.1038/s41598-018-36879-y
|View full text |Cite
|
Sign up to set email alerts
|

Self-association and subcellular localization of Puumala hantavirus envelope proteins

Abstract: Hantavirus assembly and budding are governed by the surface glycoproteins Gn and Gc. In this study, we investigated the glycoproteins of Puumala, the most abundant Hantavirus species in Europe, using fluorescently labeled wild-type constructs and cytoplasmic tail (CT) mutants. We analyzed their intracellular distribution, co-localization and oligomerization, applying comprehensive live, single-cell fluorescence techniques, including confocal microscopy, imaging flow cytometry, anisotropy imaging and Number&Bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 73 publications
2
32
0
Order By: Relevance
“…These observations are consistent with the small Gc:Gc contact patch, which appears too weak to maintain Gc dimers in solution. Similarly, membrane-anchored Gc expression in the absence of Gn was predominantly monomeric in live cells, although some Gc dimers were detected (Sperber et al, 2019). Therefore, it is likely that Gc anchoring in the context of lateral inter-spike constrains may be required for efficient Gc:Gc association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations are consistent with the small Gc:Gc contact patch, which appears too weak to maintain Gc dimers in solution. Similarly, membrane-anchored Gc expression in the absence of Gn was predominantly monomeric in live cells, although some Gc dimers were detected (Sperber et al, 2019). Therefore, it is likely that Gc anchoring in the context of lateral inter-spike constrains may be required for efficient Gc:Gc association.…”
Section: Discussionmentioning
confidence: 99%
“…A higher resolution 15.6 Å cryo-ET map allowed the docking of the Gn ectodomain into the central lobes on the tetrameric spike, at the membrane distal side, and masking the Gc fusion loops, suggesting that the 2-fold related spike-spike interactions are made by the Gc moiety (Li et al, 2016). Moreover, a central role of Gn in self-association to form spikes has recently been confirmed by number and brightness analysis in single live cells showing that separate Gn expression allows detection of Gn oligomers while separate Gc expression predominantly leads to Gc monomers and some Gc dimers (Sperber et al, 2019).…”
Section: Introductionmentioning
confidence: 92%
“…Unless otherwise specified, glycoprotein gene sequences refer to the PUUV strain. Original plasmids of signal peptide (SP)-mEYFP-Gn and SP-mEYFP-Gc were previously described (16). Plasmids encoding Gn and Gc preceded by three HA tags (HAtag-Gn, HAtag-Gc) were a gift from A. Herrmann (Humboldt Universität zu Berlin).…”
Section: Cloning and Generation Of Chimeric Proteinsmentioning
confidence: 99%
“…Early studies that aimed to localize singularly expressed Gn and Gc showed variations for different members of the Bunyavirales order (10,11). However, co-expression of both HV GPs results, in general, in their translocation to the Golgi apparatus (GA) (12)(13)(14)(15)(16). This holds true also for recombinant proteins that are not derived from a common precursor (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation